A Critical Analysis of International Students’ Experiences in Using Career Services by Adopting Neo-Racism Theory - Jiang, Yilun (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2023)
International students frequently encounter difficulties using university career services for their postgraduation career development. University career services provide very little customized and inclusive support for international students coming from different national and cultural backgrounds. By adopting neo-racism theory and drawing on findings in the literature and from my master’s thesis, I provide a critical discussion on how this lens can be applied in analyzing international students’ challenges in using career resources in the Canadian context. Pragmatically, the paper underscores the need for university career centres to adopt a culturally sensitive approach to support international students’ career development.